2024 Learning and Optimization Report - CGIAR System Organization (CGIAR System Organization, 2025)
This report is CGIAR’s primary learning report for the 2024 Technical Reporting cycle. It consolidates and synthesizes insights from a range of reflection and learning activities to highlight cross-cutting lessons. The 2024 Learning and Optimization (L&O) process was undertaken as part of CGIAR’s adaptive management methodology for Technical Reporting. Its primary objective is to identify lessons from the 2022-2024 Technical Reporting cycle and generate actionable recommendations to inform the design and delivery of the 2025-2030 Portfolio’s reporting systems, capacity-building efforts, and key products. The review identified priority recommendations across five L&O pillars to deliver on these priorities: • Conceptual aspects – Finalize revisions to the Results Framework to ensure coherent, measurable outcomes and impacts aligned with CGIAR’s 2030 targets. • Processes – Adjust timelines for greater flexibility, improve interoperability between the Performance and Results Management System (PRMS) and Program tools, clarify roles and responsibilities (especially with the integration of Window 3 [W3]/bilateral projects), and integrate quality assurance (QA) earlier in the cycle to strengthen transparency and reliability. • Systems – Advance PRMS v2 as a cohesive, user-centered platform, scale up artificial intelligence (AI) and automation to reduce reporting effort and enhance QA processes. • Capacity – Expand training and peer-learning opportunities, strengthen organizational support and engagement with Centers, and build skills for PRMS v2, AI tools, and adaptive management. • Products/Outputs – Improve report usability and readability, enhance trend analysis and Portfolio comparisons, integrate return on investment (ROI) analyses and impact/results stories, and pilot AI-generated report drafts and summaries to reduce effort and better tailor outputs to decision-makers. Together, these actions aim to reduce the reporting burden, integrate W3/bilateral results into a coherent evidence base, and reinforce accountability through transparent, verifiable links between planned targets and delivered outcomes.